Relationships between Triage Knowledge, Training, Working Experiences and Triage Skills among Emergency Nurses in East Java, Indonesia - Fathoni, Mukhamad; Sangchan, Hathairat; Songwathana, Praneed (Department of Nursing, Faculty of Medicine, Diponegoro University, 2013)
Background: Since there are increased numbers of clients with traumatic injuries and non-traumatic cases in the emergency department in Indonesia, triage skill is an essential competency required for the emergency nurses.Purposes: This study aimed to examine the level of perceived triage skills and the relationship between knowledge, training, working experience and perceived triage skills among emergency nurses.Method: Two hundred and sixty six emergency room (ER) nurses working in two secondary and two tertiary public hospitals in East Java Province, Indonesia, were recruited by purposive sampling. Data were collected using a set of questionnaires which included the Demographic Data including training and working experiences, Triage Knowledge Questionnaire (TKQ) and Triage Skill Questionnaire (TSQ). The contents of questionnaires were validated by three experts and tested for reliability. The correlation coefficient for the TKQ was 0.99 and Cronbach’s alpha coefficient of the TSQ was 0.93. The collected data were analyzed using descriptive statistics including Pearson’s product-moment correlation to examine the relationship.Result: The results showed that the majority of subjects were female (71.4%) with aged of 22 – 40 years (79.3%), educated to diploma level (94.4%). All subjects had attended Basic Life Support (BLS) and Advanced Life Support (ACLS), and about half of them had greater than 5 years working experiences in ED. Overall perceived triage skill was at a moderate level with the mean score of 75.12 (SD = 11.23). There were significantly positive correlations between triage skill and working experience (r = .27, p < .01), training experience (r = .37, p < .01), and triage knowledge (r = .38, p < .01).Conclusion: The findings provide a better understanding of triage skills among ER nurses and suggest that the continuing education and training courses related to triage and advanced management of medical emergencies for ER nurses are required in order to increase and update the triage skills in enhancing the quality of emergency care and patient safety.Key Words :Triage knowledge, triage skills, training, working experience, emergency nurse